Chiswick House - Kent, William
If Colin Campbell provided the enthusiasm for the return to "Regular Architecture," it was William Kent (1685-1748) who provided the glory. An apprenticed painter he was sent to Rome by a generous sponsor. He returned to England in 1719 with Lord Burlington (1695-1753), and was responsible with him for the building of a Palladian Villa in the gardens of Burlington's Chiswick House. Lord Burlington had employed Colin Campbell to design his London house in Piccadilly, and had thus acquired an abiding interest in Palladian architecture. The villa at Chiswick is based on Palladio's Villa Capra, at Vicenza, but the interior is more gorgeous, with its detail generously copied from the archaeological surveys then taking place in Italy.